Introduction to This Special Issue on Open Design at the Intersection of Making and Manufacturing. (2nd September 2019) - Green, David Philip; Fuchsberger, Verena; Taylor, Nick; Bjørn, Pernille; Kirk, David; Lindtner, Silvia
ABSTRACT: What is 'open design' and who gets to say what it is? In the emerging body of literature on open design, there is a clear alignment to the values and practices of free culture and open source software and hardware. Yet this same literature includes multiple, sometimes even contradictory strands of technology practice and research. These different perspectives can be traced back to free culture advocates from the 1970s to the 1990s who formulated the ideal of the internet as inherently empowering, democratizing, and countercultural. However, more recent approaches include feminist and critical interventions into hacking and making as well as corporate strategies of "open innovation" that bring end-users and consumers into the design process. What remains today seems to fall into two schools of thought. On one hand, we have the celebratory endorsements of 'openness' as applied to technology and design. On the other hand, we have a continuous and expanding critique of these very ideals and questions, where that critique identifies persisting forms of racial, gender, age, and class-based exclusions, and questions about the relationship between open design, labor and power remain largely unanswered.